KAJIAN KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJAAN PEMBANGUNAN BENDUNGAN KRUENG KEUREUTO DI KABUPATEN ACEH UTARA - Helmi Helmi; Alfiansyah Yulianur; Ella Meilianda (JURNAL TEKNIK SIPIL, 2016)
Abstract: The implementation of occupational safety and health program is one of the efforts to create a workplace that is safe, healthy and free from environmental pollution, so as to prevent or reduce rather than workplace accidents. The purpose of this research is 1) To determine the level of awareness and understanding of occupational health and safety programs, 2) To find out how the implementation of occupational safety and health program, and 3) To find out what kind of risk of work accidents happened at the project site . The scope of this study is limited to the study of occupational safety and health is applied to the construction of dams Krueng keurueto jobs in North Aceh district. The research was conducted by distributing questionnaires to 65 respondents who were directly involved in the work of this dam. Data processing is performed by analysis of frequency and relative importance index (RII). The object of research is a director of the Company; Project Manager; Field Executive; Field Supervisors and Workers / heavy equipment operator involved in Krueng Dam construction work Keureuto In North Aceh District. Based on the results of data processing and discussion, it has been able to research appropriate research objectives, namely: the level of awareness and understanding of the elements of safety and health programs of work "provision of the box first aid Workplace" occupies the most weight as high as: 4.86, for the implementation of the program health and safety "Use of Personal Protective Equipment (PPE) which is becoming a necessity among workers" with a weight of 4.79, the type of work hazard the most common is "irritation of the eyes when transporting the ground" with a weight of 2:19 while the types of risks accidents that are rare are "accidents caused by heavy equipment operational" with a weight of 1.89.Keywords : occupational safety and health , dam Krueng keureuto.Abstrak: Pelaksanaan program keselamatan dan kesehatan kerja adalah salah satu bentuk upaya untuk menciptakan tempat kerja yang aman, sehat serta bebas dari pencemaran lingkungan, sehingga dapat mencegah ataupun mengurangi dari pada kecelakaan kerja. Tujuan penelitian adalah 1) Untuk mengetahui tingkat kesadaran dan pemahaman terhadap program keselamatan dan kesehatan kerja, 2) Untuk mengetahui bagaimana pelaksanaan program Keselamatan dan Kesehatan Kerja dan 3) Untuk mengetahui apa saja jenis risiko kecelakaan kerja yang terjadi di lokasi proyek. Ruang lingkup penelitian ini dibatasi pada kajian keselamatan dan kesehatan kerja yang diterapkan pada pekerjaan pembangunan bendungan krueng keurueto di kabupaten Aceh Utara. Penelitian dilaksanakan dengan penyebaran kuesioner kepada 65 responden yang terlibat langsung dalam pekerjaan bendungan ini. Pengolahan data dilakukan dengan analisis frekuensi dan relative importance index (RII). Objek penelitian adalah Direktur Perusahaan; Project Manager; Pelaksana Lapangan; Pengawas Lapangan dan para Pekerja / operator alat berat  yang terlibat pada pekerjaan Pembangunan Bendungan Krueng Keureuto Di Kabupaten Aceh Utara. Berdasarkan hasil pengolahan data dan pembahasan, maka telah di dapat hasil penelitian sesuai tujuan penelitian yaitu: tingkat kesadaran dan pemahaman terhadap elemen-elemen program keselamatan dan kesehatan kerja ”Penyediaan kotak pertolongan pertama pada kecelakaan (P3K) ditempat kerja” menempati bobot paling tinggi yaitu: 4.86, Untuk pelaksanaan program keselamatan dan kesehatan kerja “Penggunaan Alat Pelindung   Diri (APD) yang menjadi keharusan dikalangan pekerja” dengan bobot 4.79, jenis risiko kecelakaan kerja yang paling sering terjadi adalah “iritasi pada mata saat pengangkutan tanah” dengan bobot 2.19 sedangkan jenis risiko kecelakaan kerja yang jarang terjadi adalah “kecelakaan akibat opersional alat berat” dengan bobot 1.89.Kata kunci : keselamatan dan kesehatan kerja,  bendungan krueng keureuto.